Public reason and courts / edited by Silje A. Langvatn, Mattias Kumm, Wojciech Sadurski. - Langvatn, Silje Aambø, 1976-; Kumm, Mattias; Sadurski, Wojciech, 1950- (Studies on international courts and tribunals., 2020)
Public Reason and Courts is an interdisciplinary study of public reason and courts with contributions from leading scholars in legal theory, political philosophy and political science. The book's chapters demonstrate the breadth of ways in which public reason and public justification is currently seen as relevant for adjudicative reasoning and review practices, and includes critical assessments of different ways that the idea of public reason has been applied to courts. It shows that public reason is not just an abstract theoretical concept used by political philosophers, but an idea that spurs new perspectives and normative frameworks also for legal scholars and judges. In particular, the book demonstrates the potential, and the limitations, of the idea of public reason as a source of legitimacy for courts, in a context where many courts face political backlashes and crisis of trust.